Nekaj ugotovitev o Linhartovi Miss Jenny Love - Mihurko Poniž, Katja (Slavistična revija, 2012)
The paper discusses three hitherto unknown copies of Miss Jenny Love and dramatic texts bound together With Linhart´s first published play in five different volumes, now held in the libraries in Vienna, Munich, Ausburg, and Berlin. It also includes information about the publishing house C. H. Stage, which published Linhart´s tragedy. In addition, the author presents the findings of the research into the inaugural performance of the play.
Keywords: 18.st.; history of literature; Linhart, Anton Tomaž, 1756-1795; literarna zgodovina; literarne študije; Miss Jenny Love; Slovene literature; slovenska dramatika; slovenska književnost; slovensko-nemški stiki